Spremljanje uporabe serijskih ortoz za gleženj in stopalo ter serijskih ortoz za gleženj v lekarni URI - Soča - Gorec, Petra (Rehabilitacija (Ljubljana), 2021)
Background: The purpose of the study was to determine whether persons who have been issued with serial ankle-foot orthoses (AFO) or ankle- orthoses (AO) at the Pharmacy of the University Rehabilitation Institute in Ljubljana (Pharmacy Soca) are still using the orthoses after 30 and 90 days after receiving them. We also assessed their satisfaction with the orthoses using a survey. Methods: Twenty-four people who had visited the Pharmacy Soca to receive prescribed AFOs or AOs were willing to participate and were included in the study. We used a questionnaire to follow-up the usage of, and satisfaction with, serial AFOs or AOs. The questionnaire was administered with a telephone interview 30 and 90 days after receiving the orthosis. Results: The survey was filled by nine women and 11 men with an average age of 60 years. Participants used serial AFOs or AOs for 5.9 days per week and 7.2 hours per day on average after 30 days since receiving it, and for 5.3 days per week and 8.8 hours per day on average after 90 days since receiving it. The analysis did not confirm statistically significant differences. The majority of complains from the participants regarding the orthoses were about the fitting procedure, unbreathable material (plastic) and poor durability of the straps. Conclusion: The results of the study will be of help in our further work, as we will be able to focus on the causes of potential non-use and anticipate possible user concerns in advance, which should lead to better rehabilitation outcome of each individual.
Keywords: anketa; duration of use; Foot Orthoses; foot-drop; orthoses; ortoze; padajoče stopalo; satisfaction; survey; therapeutic use; trajanje uporabe; zadovoljstvo